2020
DOI: 10.36709/jpm.v11i1.9901
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Game Edutainment Berbasis Smartphone Sebagai Media Pembelajaran Berorientasi Pada Kemampuan Berpikir Kreatif

Abstract: Penelitian ini bertujuan untuk mendeskripsikan langkah pengembangan serta melihat kelayakan dari sebuah game edutainment berbasis smartphone yang digunakan sebagai media pembelajaran berorientasi pada kemampuan berpikir kreatif siswa. Jenis penelitian ini adalah penelitian pengembangan dengan prosedur pengembangannya menggunakan model ADDIE. Adapun prosedur pengembangannya terdiri dari analisis masalah, analisis materi, validasi kesenjangan kinerja, desain produk, validasi ahli media dan ahli materi, uji coba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
2
0
2
Order By: Relevance
“…This result is in line with the result of previous research which revealed that interactive multimedia has a positive impact on students' mathematical communication skills [29]. Other research also revealed that interactive multimedia not only could improve students' mathematical communication skills, but also effectively improve students' creative thinking skills [30].…”
Section: Discussionsupporting
confidence: 90%
“…This result is in line with the result of previous research which revealed that interactive multimedia has a positive impact on students' mathematical communication skills [29]. Other research also revealed that interactive multimedia not only could improve students' mathematical communication skills, but also effectively improve students' creative thinking skills [30].…”
Section: Discussionsupporting
confidence: 90%
“…According to the analysis, teachers at SMPN 1 Kencong do not utilize learning materials, leading to low creative thinking skills in students. Previous research by Mahfi (2020) highlighted the lack of specific media to support students' creative thinking. Following the design phase, the development stage was initiated to realize the learning materials.…”
Section: E Evaluationmentioning
confidence: 99%
“…In addition, the existence of learning media that functions as a tool in presenting subject matter is also expected to improve students' creative thinking skills. According to Dewi and Masrukan (2018) in Mahfi (2020), creative thinking is an activity carried out by someone in solving a mathematical problem in a variety of ways. Creative thinking is a habit of thinking that is learned by paying attention to different points of view, which helps students to have imagination, to show new possibilities, to open themselves to different points of view and to come up with unusual ideas.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian dan pengembangan atau research and development (R&D) adalah jenis penelitian ini. Dalam penelitian ini kami menggunakan model penelitian ADDIE yang meliputi 5 langkah yaitu: analisis, desain, pengembangan, implementasi dan evaluasi dikembangkan oleh Dick & Carey (Mahfi et al, 2020). Kelima langkah ini diterapkan secara sistematis.…”
Section: Metode Penelitianunclassified